2015
DOI: 10.3233/jpd-140515
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Long-term Parkinson’s Disease Survivors with 20 Years of Disease Duration and Beyond

Abstract: Abstract.Background: Parkinson's disease (PD) patients with 20 years or more survival are not well characterized. Objective: To evaluate PD-20 patient characteristics and identify areas for improvement of their health care. Methods: The international, multicenter National Parkinson's Foundation Quality Improvement Initiative (NPF-QII) study database was queried to identify PD-20 subjects. Demographic and clinical data were analyzed. Results: We identified 187 PD-20 subjects (55% men) representing 4% (187/4,61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
5
30
1
Order By: Relevance
“…Interestingly, findings from this study revealed that only 1 out of the 36 participants exhibited a TD phenotype, which might be less than would be anticipated from previous studies suggesting that such patients are conferred with a more benign course and slower disease progression 15,17,40,41 . While the overrepresentation of patients with non-TD feature may reflect an artefact of how the motor phenotypes were classified in the present study, such overrepresentation more likely suggests the transition of predominant motor features over the long disease course.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, findings from this study revealed that only 1 out of the 36 participants exhibited a TD phenotype, which might be less than would be anticipated from previous studies suggesting that such patients are conferred with a more benign course and slower disease progression 15,17,40,41 . While the overrepresentation of patients with non-TD feature may reflect an artefact of how the motor phenotypes were classified in the present study, such overrepresentation more likely suggests the transition of predominant motor features over the long disease course.…”
Section: Discussioncontrasting
confidence: 84%
“…To date, only a limited number of studies have investigated the clinical features of PD patients with disease duration of 20 years or more, as this is a small number of people with PD. 10,17 We identified 36 such patients from a cohort of 2327 patients (1.5%) and investigated the frequency of dementia within them using data from assessments ≥20 years from diagnosis. Using the MDS Level 1 PDD criteria, only 7 of the 36 (19%) participants met criteria for PDD after 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As treatments for Parkinson’s disease movement symptoms advance and patients maintain an active lifestyle for longer disease duration [30], even the earliest cognitive impairments are an increasing source of disability [6]. Our findings suggest that when a PD patient reports a slight degree of cognitive impairment, declines in visuospatial function and verbal memory are most likely to be driving this complaint relative to other cognitive domains.…”
Section: Discussionmentioning
confidence: 85%
“…In the case of juvenile or early onset PD before the age of 35 years, a further genetic analysis, even in the absence of a positive family history, as typically related to an autosomal recessive inheritance with unaffected parents, is worthwhile (Sheerin et al 2014). Early onset patients typically present with a more benign disease course and are less frequently subject to cognitive impairments; however, motor fluctuations are typically observed and can justify interventional treatment options within the advPD concept (Hassan et al 2015) Generally, these forms of PD are typically rare and as a chronic-progressive neurodegenerative disease, most patients are diagnosed at a rather advanced age. Thus, at the age of 65, the incidence amounts to approximately 50 in 100,000, at age 75–150 in 100,000, and at age 85–400 in 100,000 (de Lau et al 2006; Pringsheim et al 2014).…”
Section: Strategies To Define Diseases Stagesmentioning
confidence: 99%